Effect modification by life's essential 8 on the association between hearing loss and atherosclerotic cardiovascular disease among US adults - Shujie Li; Yiping Liu; Shuai Xia; Honglin Li (Preventive Medicine Reports)
Objective: This study aimed to evaluate whether associations between hearing loss and atherosclerotic cardiovascular disease (ASCVD) were modified by Life's Essential 8 (LE8) in US adults. Methods: A total of 10,867 participants from five cycles of the National Health and Nutrition Examination Survey conducted between 2005 and March 2020 were included in the analysis. Multivariable logistic regression models were applied to examine the relationship between hearing loss, LE8, and ASCVD. Interaction analyses were performed to determine whether the association between hearing loss and ASCVD was modified by cardiovascular health. Results: About half (50.1 %) of the participants were male, with a mean age of 49.2 ± 17.7 years, and 41.3 % white. The weighted prevalence of ASCVD was 9.5 % and audiometry-measured hearing loss was 19.8 %. Hearing loss was independently associated with higher odds of ASCVD (OR 1.44, 95 % CI 1.16, 1.79). Interaction analysis indicated that the association between hearing loss and ASCVD was evident in individuals with low (< 50) or moderate (50–80) LE8 scores, but not in those with high LE8 scores (≥ 80) (Pinteraction = 0.008). Conclusions: This study observed a significant association between hearing loss and ASCVD, with the strength of the association varying across cardiovascular health status.